Branding Strategy of Local Screen Printing Plastic Bag MSMEs in Facing Global Market Competition: Branding Strategy of Local Screen Printing Plastic Bag MSMEs in Facing Global Market Competition - Tohiroh, Tohiroh; Sutariyono, Sutariyono; Mulasih, Siti; Alfarisi, Sya’ban Maulana; Muharifah, Isnaini (Daengku: Journal of Humanities and Social Sciences Innovation, 2025)
The Micro, Small, and Medium Enterprises (MSMEs) industry in Indonesia plays an important role in the country's economy, especially in the creative and manufacturing industries. One of the products that is increasingly developing is local screen-printed plastic bags, but faces increasingly tight global market competition. The purpose of this study is to identify and analyze branding strategies implemented by local screen-printed plastic bag MSMEs in competing in the global market. This study uses a qualitative approach with a case study method on MSME actors engaged in the screen-printed plastic bag industry. The results of the study indicate that branding strategies are essential to increase the competitiveness of MSMEs in the global market. It is important for MSMEs to pay attention to global trends such as tourism and environmentally friendly technology to attract the attention of global consumers. This study also found that brand strengthening and consistent communication with consumers through digital platforms can be a significant competitive advantage. The implication of this study is that MSMEs need to be more adaptive to changes in the global market and take advantage of various opportunities to improve their position in the international market through innovative and planned branding strategies.